Social Media Analysis as a Marketing Strategy in Online Marketing Business - Rahardja, Untung (Startupreneur Business Digital (SABDA Journal), 2022)
Information technology in the last few years has experienced fairly rapid development. During this period, a a platform that allows people around the world to connect with each other called social media. Today, Facebook, Twitter and Instagram are social media that is experiencing the fastest development. The three social media has begun to be widely used to promote a product and be used as a one of the marketing strategies by several business people. The purpose of this journal is to: to explore the use of social media especially Facebook, Twitter and Instagram in online business marketing strategy. Research is expected to be input for business people who want to use social media as one of the media promotion of services and products. This study aims to find out how the use of social media as a business strategy by some business people online based.